Drying characteristics and mathematical model of ultrasound assisted hot-air drying of carrots - Denglin, Luo; Juan, Liu; Yunhong, Liu; Guangyue, Ren (International Journal of Agricultural and Biological Engineering, 2015)
In order to improve the heat and mass transfer process in hot-air drying, power ultrasound was coupled directly to hot-air drying of fresh carrot slices. The effects of ultrasonic power, radiation distance, hot air velocity and temperature on drying characteristics were studied. In addition, the Page equation was used to fit the ultrasound assisted hot-air drying process of the carrot slices. The results showed that the drying rate of carrot slices increased with the increase of ultrasound power and the decrease of radiation distance. Power ultrasound had a greater enhancement on hot-air drying at lower air velocity (0.5 m/s) and temperature (40ºC), especially at the middle and later periods (controlled by internal diffusion). The drying time of carrot slices using ultrasound assisted hot-air drying was shortened by 37.5% compared to that using hot-air drying at the condition with power of 150 W, radiation distance of 15 cm, air velocity of 1.0 m/s and temperature of 40ºC. All test indicators of the model meet the accuracy requirements, which show that the model can better fit the experimental values. Keywords: power ultrasound, hot-air drying, carrot slices, drying rate, model DOI: 10.3965/j.ijabe.20150804.1962 Citation: Luo D L, Liu J, Liu Y H, Ren G Y. Drying characteristics and mathematical model of ultrasound assisted hot-air drying of carrots. Int J Agric & Biol Eng, 2015; 8(4): 124－132.